ANALISIS KEBUTUHAN SISWA PENGGUNAAN MODEL GAME BASED LEARNING BERBASIS ROBLOX PADA PELAJARAN FIKIH DI SEKOLAH - Ari Riyadi; Gilang Maulana Jamaludin (As-Sulthan Journal of Education, 2026)
The development of information and communication technology today requires innovation in learning, including in the subject of Fiqh. A less interactive learning process has the potential to reduce students' motivation and understanding of the material in Fiqh subjects. This study aims to analyze students' needs for the use of Roblox-based Game Based Learning  models in Fiqh subjects in schools. This research uses the Research and Development (R&D) method with the ADDIE model, which is focused on the needs analysis stage. The research subjects consisted of 15 students of class XI RPL at SMKS Karya Bakti Sindang. The data collection technique was carried out through the distribution of questionnaires which included pedagogical, technical, cognitive, interest and motivation aspects of learning, as well as evaluative, with a Likert scale of 1-5. The results showed that all aspects obtained an average score above 3, with most indicators being in the "most needed" to "urgently needed" category. These findings indicate that students have technical readiness, high interest, and a need for more interactive Fiqh learning, utilizing visual media, and game-based learning. The results of this research provide a conceptual basis for the development of Roblox-based Fiqh learning media in Fiqh subjects, as well as a strong basis to continue at the next stage in  this Research and Development (R&D) research.